Are Christian/religious people poor tippers?. Issue 5 (3rd April 2013) - Lynn, Michael; Katz, Benjamin
Abstract A web‐based survey was used to assess the relationships of religious faith and frequency of church attendance with tipping under conditions of good and bad service. Results indicated that Jews and those with no religion tipped more than Christians and members of other religions, but that the vast majority of Christians tipped at or above the normative 15% of bill size. Worship frequency also significantly interacted with service quality such that the tips of those who frequently worship vary with service quality less than the tips of those who worship less frequently. The practical implications of these results for service workers and restaurants or other service businesses with a large religious clientele are discussed.